Penerapan Khutwatut Tadris Terhadap Kemampuan Berbahasa Arab di Pondok Pesantren Darul Amien TMI - Alfiannor; afifah, Nor (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2025)
ABSTRACT The Khutwatut Tadris program at Darul Amien TMI (Tarbiyatul Mu'allimin WalMu'allimat Al-Islamiyah) Islamic Boarding School is an integrative learning initiative that aims to improve the active Arabic language skills of students while developing their pedagogicalcompetence as prospective educators. This program is based on the need for educators who not only master religious material, but are also able to teach with effective methods and speak Arabic fluently. This research uses a descriptive qualitative approach with data collection techniques through participatory observation, in-depth interviews with santri and supervising ustadz, as well as document analysis of lesson plans and teaching evaluation notes. The data were analyzed thematically to identify the impact of the program on the students' Arabic language ability and teaching skills. The findings show that students experienced a significant increase in Arabic fluency after participating in the program, especially in the aspect of maharah al-kalam (speaking ability). In addition, students reported increased confidence in managing the class and delivering the material. The main challenges include time constraints and difficulty in mastering vocabulary, which are overcome through intensive guidance and habituation to the Arabic-speaking environment in the pesantren. Khutwatut Tadris proved to be effective as a practice-based learning model that integrates linguistic and pedagogical aspects. The success of the program is supported by the role of ustadz as facilitators and evaluators, as well as the communicative language teaching (CLT) approach applied. The implications of this study highlight the importance of Arabic immersive environments and continuous teaching training in the pesantren curriculum.